A whole new mind : moving from the information age to the conceptual age - Pink, Daniel H. (New York : Riverhead Books, 2005)
Explores how the business world is changing in the twenty-first century, becoming more "right-brain" based and allowing people more creative and artistic than earlier generations succeed more than those with left-brain dominance.
Includes bibliographical references and index.
Choice.
Adult
Keywords: Creative thinking; Success -- Psychological aspects; Creative thinking; Success -- Psychological aspects